Decomposing Inequality Under Alternative Concepts Of Resources: Greece 1988 - Mitrakos, Theodore; Tsakloglou, Panos (Journal of Income Distribution®, 1999)
The structure of inequality in Greece is analyzed using the information of a survey which contains both consumption and income data. Due to life-cycle factors and measurement errors, the correlation between the two variables is not very high and, hence, and approximation of the “permanent income” of the population members is attempted. Although the level of inequality of either the distribution of consumption expenditure or the distribution of disposable income, the structure of inequality in Greece is only slightly affected by the choice of distribution. Copyright 2000 Elsevier Science Inc. All rights reserved